A critique on the implementation of whole school evaluation policy in Limpopo province - Mbalati, Timothy (My University, 2010)
The purpose of this study was to critique the level of influence the Whole School Evaluation (WSE) policy framework had on the quality of teaching and learning in the Limpopo Province schools. Limpopo Province comprises of five districts with different learner performance levels. At the time when this study was conducted Sekhukhune District had the worst learner performance results followed by Mopani. Up to the early 1990s schools in South Africa became sites of struggle against Apartheid, as most citizens rejected a system of government that was characterized by inequality (Seedat, 2004:190). As a result (Herselman & Hay, 2002: 239), many schools in South Africa, including those in Limpopo Province were destroyed morally and physically to the level of becoming less productive and some totally dysfunctional. The WSE policy is a mechanism that was developed to address the above problem. In addition, among others, the WSE policy was aimed at the development of a collaborative approach that would enable a school (individually or as a cluster) to deliver, quality services to the community , including the improvement of circumstances in schools that could create conditions for the facilitation of quality education within a particular given school period. All schools in Limpopo Province were made aware of the WSE policy framework and how it was implemented. As early as 2003 the Quality Assurance Directorate ensured that all schools had the relevant material and policy documents for implementing WSE. Circuit Managers, School Principals and three educators per school were subjected to an intensive training programme on how WSE policy framework is implemented. The empirical research was done through the observation of educators and learners within their schooling environment, perusal of primary and secondary documents and interviewing of the policy implementing agents, i.e. the Principals, Educators and Circuit Managers. The study: • Indicated that there is a serious problem to implement WSE policy in schools; • Exposed school managers, SMTs and educators` incompetence to comply with the prescription of the policy; • Revealed the inhibitors of the effective implementation of WSE process; • Aroused the awareness to the researcher of the operational discord that was experienced by the schools that had a problem in complying with the WSE policy requirements. • Some schools were reluctant to comply with the prescripts of the policy. • Schools had their School Improvement Plans (SIPs), School Development Plans (SDPs) and Academic Performance Improvement Plans (APIPs) but their day-to-day operations in no way showed compliance to what was put on the improvement document as their operational guide. Furthermore, the study clearly argue that quality education can only exist in situations where school communities and education officials are equally striving at reconciling the complex and dynamic relationships that exist between the learner, the centre of learning or school, the broader education system and the social, political and economic context of which they are part. The study developed, on completion, a full programme that can clearly show elements in our education system the negatively impacts on the desired progress, based on the findings in the Limpopo Province. In conclusion, the study revealed challenges that impacted negatively on the implementation of the WSE policy framework in the Limpopo Province Schools. As a way forward strategies were suggested that if complied with the WSE policy framework could be successfully implemented and quality teaching and learning enhanced.
Thesis (PhD.(Education)) --University of Limpopo, 2010
Keywords: Policy Implementation; School Evaluation Policy; 371.200968; School management and organization; Educational planning